The Relation between the Concepts of Recreation and Tourism - Bachvarov, Marin; Dziegieć, Elżbieta (Turyzm/Tourism, 2005)
The authors present a comparative analysis of the relation between the concepts of tourism and recreation in the context of leisure time and also the spaces in which they occur. A review of many publications in Polish, French and English indicates that there is no agreement as to whether recreation includes everything leading to physical and mental “regeneration”, or whether it should be limited to active outdoor recreation. Although recreation and tourism activities may be very different they often occur in one and the same space. Therefore, recreation as a part of tourism which actually combines the qualities of both can be discussed from the perspectives of the participant, the economic agent and the space where it occurs.